Improving fuel efficiency of shunting diesel locomotive when applying electronic control system of fuel injection - I. A. Kuznetsova; E. E. Kossov (Вестник Научно-исследовательского института железнодорожного транспорта)
When creating a new rolling stock or during its modernization it is important preliminarily to properly assess its operational efficiency, depending on the technical improvements. Changing the way of energy supply of traction is very important - for example, hybrid engines or two/three power units is used instead of one. The article proposes a new approach to the problem of assessing the effectiveness of operational work of shunting locomotives. Shunting operation is represented as the sum of random single modes, in which the processes in the power plant can be modeled with any degree of accuracy. Summation of performance indicators in individual modes according to the characteristics of random processes allows obtaining an overall assessment of technical and economic indicators of the locomotive in operation. The paper shows results of comparative assessment of the fuel economy of a diesel locomotive ChME3 in operating set of equipment and with installed electronic fuel injection control system (ESUVT. 02), obtained by modeling the working processes of the power plant and auxiliary equipment shunting locomotives in operation modes. Executed calculations show that in the operation of diesel locomotive ChME3 equipped with ESUVT. 02 system saves up to 10.2 % of fuel, particularly by reducing fuel consumption at idle. Application of a new methodology for assessing technical and economic indicators of locomotives in operation allows, in addition to fuel consumption, evaluating a number of other indicators.